Building Java 8 web applications with microservices (LiveLessons., 2016)
"Building Java 8 Web Applications with Microservices LiveLessons Workshop utilizes live code demonstration to build a fully functional application using minimal external dependencies and Java 8. This application consumes a real-time feed of high-velocity data, contains services that make sense of the data, and presents it in a JavaFX dashboard. Along the way, you'll encounter Java 8 streams, lambdas, new ways of working with collections, and the new date and time API."--Resource description page.